Rozwiązanie:
[tex]f(x)=-(x-3)(x+1)=-x^{2}+2x+3[/tex]
[tex]a)[/tex]
Miejsce zerowe:
[tex]-(x-3)(x+1)=0\\x=3 \vee x=-1[/tex]
[tex]b)[/tex]
[tex]p=-\frac{b}{2a}=\frac{-2}{-2}=1\\q=f(p)=f(1)=-1+2+3=4[/tex]
[tex]c)[/tex]
Postać kanoniczna:
[tex]f(x)=-(x-1)^{2}+4[/tex]
[tex]d)[/tex]
Wykres w załączniku.
[tex]e)[/tex]
Zbiór wartości:
[tex]Y=(-\infty,4>[/tex]
[tex]f)[/tex]
Monotoniczność:
Funkcja rośnie dla [tex]x \in (-\infty,1>[/tex]
Funkcja maleje dla [tex]x \in \ <1,\infty)[/tex]
[tex]g)[/tex]
Równanie osi symetrii:
[tex]x=1[/tex]